Dendrochronological dating of buildings in 's-Hertogenbosch (Bulletin KNOB, 1993)
In 's-Hertogenbosch structured building-historical research has been executed since 1975. For this purpose dendrochronological dating of building timber has been executed for a few years now. By means of these exact dates we have acquired a better insight into the building history of the separate buildings and into the town structure as a whole.Details such as the setting up of profiles, constructions, timber connections, counting marks and stone formats - which were the dating possibilities until recently - can now be compared better as regards age. In this article the results are discussed of building-historical research in nine houses in the town centre of 's-Hertogenbosch.